2009
DOI: 10.1109/lmwc.2009.2027098
|View full text |Cite
|
Sign up to set email alerts
|

Phase Locked BWO System for Open Resonator Measurement in D-Band

Abstract: The combination of a D-Band phase-locked backward-wave oscillator (BWO) with a spectrum analyzer for measurement of permittivity and low loss-tangent is presented. For measuring low loss tangent material, such as CVD diamond and high purity semi-insulating ( ) 4SiC, at millimeter wave ranges, it is necessary to precisely measure an increase of a few kHz in a line-width of 200 kHz. We describe a phase-locked loop with frequency conversion that combines a BWO source and a microwave spectrum analyzer to obtain li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Radiation of the MMW signal from the BWO leaves the output horn, passes a wire-grid polarizing beam splitter, with one polarization directed to the resonator measurement system and the orthogonal polarization utilized for the PLL system. The RF power for the PLL system is focused by a TPX lens into a horn that feeds the waveguide mixer [9].…”
Section: The Pll-bwo Open Resonator System and Measured Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation of the MMW signal from the BWO leaves the output horn, passes a wire-grid polarizing beam splitter, with one polarization directed to the resonator measurement system and the orthogonal polarization utilized for the PLL system. The RF power for the PLL system is focused by a TPX lens into a horn that feeds the waveguide mixer [9].…”
Section: The Pll-bwo Open Resonator System and Measured Resultsmentioning
confidence: 99%
“…However, the phase noise of a BWO output is influenced by the velocity spread of the electron beam, which can lead to a poor phase noise performance. Fortunately, the MMW frequency synthesizing method for BWO, which utilizes the technology of phase-or frequency-locked to a stable source or cavity, is applied to optimize the dynamic range and the accuracy of the open resonator system considerably [7][8][9]. Analogous works have been published earlier to improve the performance and to achieve higher sensitivity of measurements, one of the papers reported that the phase locked loop (PLL) reduces the uncertainty of the BWO frequency down to 1.0 kHz in a broadband frequency range (45-200GHz) [2].…”
mentioning
confidence: 99%
“…The AD4007 chip contains pre-scale, a phase-frequency detector (PFD) and a charge pump (CP). In this chip, the phase of the divided IF signal is compared to an oven-stabilized crystal oscillator, any difference generates an error signal, will input to a third order active low pass filter (LPF) and control the BWO [9].…”
Section: The Cp-pll Bwo Systemmentioning
confidence: 99%